Evaluation of power transfer efficiency for a high power inductively coupled radio-frequency hydrogen ion source. (15th February 2018) - Jain, P; Recchia, M; Cavenago, M; Fantz, U; Gaio, E; Kraus, W; Maistrello, A; Veltri, P
Abstract: Neutral beam injection (NBI) for plasma heating and current drive is necessary for International Thermonuclear Experimental reactor (ITER) tokamak. Due to its various advantages, a radio frequency (RF) driven plasma source type was selected as a reference ion source for the ITER heating NBI. The ITER relevant RF negative ion sources are inductively coupled (IC) devices whose operational working frequency has been chosen to be 1 MHz and are characterized by high RF power density (∼9.4 W cm −3 ) and low operational pressure (around 0.3 Pa). The RF field is produced by a coil in a cylindrical chamber leading to a plasma generation followed by its expansion inside the chamber. This paper recalls different concepts based on which a methodology is developed to evaluate the efficiency of the RF power transfer to hydrogen plasma. This efficiency is then analyzed as a function of the working frequency and in dependence of other operating source and plasma parameters. The study is applied to a high power IC RF hydrogen ion source which is similar to one simplified driver of the ELISE source (half the size of the ITER NBI source).